NOBLADS—External Validation of a Risk Scoring System for Severe Acute Lower Gastrointestinal Bleeding. Issue 2 (February 2022) - Brito, Mariana; Patita, Marta; Nunes, Gonçalo; Canhoto, Manuela; Fonseca, Jorge
Abstract : BACKGROUND: Acute lower gastrointestinal bleeding is a common cause of hospital admission. NOBLADS is a lower gastrointestinal bleeding clinical risk score. OBJECTIVE: This study aimed to externally validate NOBLADS in predicting severe acute lower gastrointestinal bleeding and clinical outcome. DESIGN: Observational retrospective study. SETTING: This study was performed in a single large tertiary hospital. PATIENTS: Patients who were admitted with acute lower gastrointestinal bleeding during a 15-month period and underwent endoscopic evaluation were included. Patients with chronic lower gastrointestinal bleeding or acute lower gastrointestinal bleeding who were admitted for other conditions were excluded. MAIN OUTCOME MEASURES: Primary outcome was acute severe lower gastrointestinal bleeding (classified as severe if requires transfusion of >2 units of packed red blood cells and/or produces a >20% hematocrit fall). Secondary outcomes: red blood cells requirement, therapeutic intervention and hospital stay duration. NOBLADS score was applied to all patients. Its accuracy to predict acute severe bleeding and secondary outcomes were studied using receiver operating characteristic analysis. RESULTS: A total of 173 patients (50.3% males, age 69 ± 17 years) were included. The most common lower gastrointestinal bleeding etiologies were diverticular bleeding (18.5%) and ischemic colitis (15.6%). Fifty patients (28.9%) presented criteria for severe bleeding and 33 patients required instrumental intervention: endoscopic (n = 28), surgical (n = 4), and radiologic (n = 1) therapy. NOBLADS score was significantly different according with acute lower gastrointestinal bleeding causes ( p < 0.001) and accurately predicted severe bleeding (area under the receiver operating characteristic curve 0.923 ± 0.018 ( p < 0.001)). NOBLADS ≥2 detected acute severe lower gastrointestinal bleeding with 100% sensitivity/62.4% specificity, identifying the need for higher red blood cells requirement (3.6 vs 0.08, p < 0.001), therapeutic intervention (38% vs 13%, p < 0.001), and longer hospital stay (12.8 vs 3 days, p < 0.001). LIMITATIONS: Unicenter retrospective study; number of unprepared sigmoidoscopies/left side colonoscopies; comparison between NOBLADS and other scoring systems was not performed. CONCLUSION: NOBLADS is a practical, highly accurate tool and predicts the need of in-hospital management, early colonoscopy, red blood cells transfusion, and longer hospital stay in patients admitted with acute lower gastrointestinal bleeding. See Video Abstract at http://links.lww.com/DCR/B748 . NOBLADS: VALIDACIÓN EXTERNA DE UN SISTEMA DE PUNTUACIÓN DE RIESGO PARA HEMORRAGIA DIGESTIVA BAJA AGUDA GRAVE ANTECEDENTES: La hemorragia digestiva baja aguda es causa común de admisión hospitalaria. NOBLADS es una puntuación de riesgo clínico de hemorragia gastrointestinal baja. OBJETIVO: Este estudio tuvo como objetivo validar externamente NOBLADS en la predicción de hemorragia digestiva baja aguda grave y sus resultados clínicos. DISEÑO: Estudio observacional retrospectivo. AJUSTE: Realizado en un gran hospital terciario. PACIENTES: Se incluyeron todas aquellas personas ingresados con hemorragia digestiva baja aguda durante un período de 15 meses y que fueron sometidos a evaluación endoscópica. Se excluyó la hemorragia digestiva baja crónica o la hemorragia digestiva baja aguda en pacientes ingresados por otras afecciones. PRINCIPALES MEDIDAS DE RESULTADO: El resultado pricipal fue la hemorragia digestiva baja grave aguda (clasificada como grave si requiere >2 transfusiones de glóbulos rojos y / o produce una caída del hematocrit >20%). Las medidas de resultados secundarias fueron: requerimiento de glóbulos rojos, intervención terapéutica y duración de la estancia hospitalaria. Se aplicó la puntuación NOBLADS a todos los pacientes. Se estudió su precisión para predecir la hemorragia aguda grave y los resultados secundarios mediante análisis ROC. RESULTADOS: Se incluyeron 173 pacientes (50, 3% varones, edad 69 ± 17 años). La etiología de hemorragia digestiva baja más frecuentes fueron: la hemorragia de orígen diverticular (18, 5%) y la colitis isquémica (15, 6%). 50 pacientes (28, 9%) presentaron criterios de sangrado severo y 33 pacientes requirieron intervención instrumental: terapia endoscópica ( n = 28), quirúrgica ( n = 4), radiológica ( n = 1). La puntuación NOBLADS fue significativamente diferente según las causas de hemorragia digestiva baja aguda ( p <0, 001), siendo precisa para predecir hemorragia grave (AUC 0, 923 ± 0, 018 ( p <0, 001). NOBLADS ≥2 detectó hemorragia digestiva baja aguda grave con 100% de sensibilidad / 62, 4 % de especificidad, identificando la necesidad de mayor requerimiento de glóbulos rojos (3.6 vs 0.08, p <0.001), intervención terapéutica (38% vs 13%, p <0.001) y estadía hospitalaria más prolongada (12.8 vs 3 días, p <0.001). LIMITACIONES: Estudio retrospectivo Unicentrico; número de sigmoidoscopias / colonoscopias del lado izquierdo no preparadas; no se realizó comparación entre NOBLADS y otros sistemas de puntuación. CONCLUSIÓN: NOBLADS es una herramienta práctica y altamente precisa que predice la necesidad de manejo hospitalario, colonoscopia precoz, transfusión de glóbulos rojos y estadía hospitalaria más prolongada en pacientes ingresados con hemorragia digestiva baja aguda. Consulte Video Resumen en http://links.lww.com/DCR/B748 . (Traducción—Dr. Xavier Delgadillo )